Anthropometric Prediction Equations for Estimating Muscle Mass of Elderly Women (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Muscle Mass (MM) has an important role in health and physical performance. There are many MM prediction equations, but none is formulated in Indonesia. This study aimed to develop Anthropometric Equations (AE) prediction for MM. A cross sectional study was used to formulate AE prediction through multiple regression analysis.Â The significance of observed differences between predicted and actual MM was tested by t test while level of agreement was assessed by Bland Altman plot. A significant correlation was found between MM and height, body mass index, calf/arm/waist circumferences, and waist hip ratio (p0.05).Â Regression analÂ¬ysis indicated that age, height, and Mid Arm Circumference (MAC) contributed significantly to MM. The resulting equation was MM (kg) = -10.22+(-.097x age)+(0.16xheight)+(0.30xMAC). There was no significant difference between actual and predicted MM results, and both had significant correlation. These results suggest that age, AP related to MM and AE provide valid prediction of MM for healthy elderly women in Jakarta.